Relationship between depression and sex steroid hormone among women with epilepsy - Ogunjimi, Luqman; Alabi, Akinyinka; Oyenuga, Ibironke; Ogunkunle, Jeremiah; Kasumu, Emmanuel; Ogunsanya, Oluwaseun; Oluseyije, Oluwatobiloba; Ogunbayo, Pelumi; Idume, Omorojo; Kasali, Adeola; Adesi, Sarah; Oyebowale, Mariam; et al. (Frontiers in Neuroscience, 2024)
Sex steroid hormones are emerging significant biomarkers of depression among Women with Epilepsy (WWE) with promising prognostic potential and therapeutic end point. Therefore, the study is aimed at exploring the association between sex steroids hormones, Anti-seizure Medication (ASM) and depression among WWE. A baseline questionnaire was used to obtain socio-demographics and clinical characteristic from one hundred and twelve (112) WWE and 50 age matched healthy control. The diagnosis of epilepsy and Electroencephalography (EEG) description was based on 2017 International League Against Epilepsy (ILAE) criteria. Blood samples were collected from cases and control during Luteal Phase (LP) and Follicular Phase (FP). The Zung Self-Rating Depression Scale (ZSRDS) was used to assess depression. The prevalence of depression among WWE is 18.8%, with a significant difference between the level of formal education (p0.000), age (p0.000) and mean ZSRDS (p0.000) among cases and control. There is a statistical difference in hormonal levels between cases and control with regards to higher testosterone [3.28±9.99 vs 0.31±0.30; p0.037], lower FP prolactin [16.37±20.14 vs 17.20±7.44; p0.778] and lower LP prolactin [15.74±18.22 vs 17.67±7.27; p0.473]. Testosterone(p0.024), FP Follicle Stimulating Hormone (FSH)(p0.009), FP Estradiol(p0.006), LP FSH(p0.031), LP Progesterone(p0.023), and LP Prolactin(p0.000) were associated with depression. However, only prolactin (p0.042) and testosterone (p0.000) predicts depression among WWE. There was higher mean depression score, lower prolactin and higher testosterone level among cases compared to control. Furthermore, there was lower prolactin and higher testosterone level in Carbamazepine (CBZ) group compared to Levetiracetam (LEV) groups.